The evaluation of epicardial adipose tissue radiodensity according to age - Ocal, Arslan; Saricam, Ersin; Dursun, Ali Doğan; Soyal, M.F.Tolga; Şahin, Hakkı Serkan; Sarıyıldız, Gulcın (Journal of Surgery and Medicine, 2020)
Aim: The grading of fatty degeneration by cardiac computerized tomography (CCT) is an important bioradiological marker to discriminate biological characteristics. Epicardial adipose tissue (EAT) degeneration has been accused of causing heart disease. However, the relationship between age and EAT radiodensity is not well known. In this study we examined epicardial adipose tissue radiodensity with CCT. Methods: A total of 147 subjects who underwent contrast-enhanced evaluation of coronary arteries with CCT between Jun 2018-July 2019 due to intermediate probability of coronary artery disease (CAD) were included in this retrospective cohort study. The radiodensities of three epicardial regions (right atrioventricular groove, posterior interventricular groove, and anterior epicardial area) and individual subxiphoid fat radiodensity ratios were obtained. Group comparisons were made according to 10-year-periods (between 10- 80 years of age). Results: We found that epicardial adipose tissue/ subxiphoid fat radiodensity ratio decreased with increasing age. After the 3rd decade, we detected a negative correlation between EAT/subxiphoid fat radiodensity ratio (r=-0.11). The radiodensity ratios of patients between 20-30 and 30-40 years of age in the LCX, RCA and anterior epicardial regions were 1.71 (0.14) and 1.06 (0.40) (P<0.001), 1.71 (0.20) and 1.04 (0.30) (P<0.001), and 1.70 (0.07) and 1.17 (0.42), respectively (P<0.001). Conclusion: EAT radiodensity ratio changes are associated with aging. Increased age is negatively correlated with EAT radiodensity ratio, which is considered fat degeneration. We realized that those changes occurred sharply after the third decade.